دراسة مقارنة للإمكانات الزراعية المتاحة بين الأردن وسورية - خدام منذر; يعقوب غسان; الحمايده عوض (Latakia University Journal -Biological Sciences Series, 2018)
إن مطلب التكامل الإنتاجي والاقتصادي بين الدول العربية، هو من المطالب الراهنة والاستراتيجية خصوصا" في ظروف العولمة. ونظرا" لاتساع الفجوة الغذائية على مستوى الوطن العربي ككل، وعلى مستوى كل دولة، كان لا بد من البحث عن إمكانيات زراعية غير مستفاد منها، أو عن تفعيل وزيادة كفاءة الانتفاع بالموارد الزراعية المتاحة، وتكاملها. وبالفعل فقد بينت الدراسة ضعف كفاءة استغلال الموارد الزراعية المتاحة في الأردن وسورية، وكذلك وجود إمكانات زراعية غير مستفاد منها مثلا"؛ وجود مساحات كبيرة من الأراضي الصالحة للزراعة في الأردن لا تزال خارج نطاق الزراعة، وكذلك استمرار وجود نظام الراحة للأراضي في سورية، هذا بالإضافة إلى هدر الموارد المائية المتاحة في سورية من جراء استخدام نظام الري بالغمر. ولقد بينت الدراسة أيضا" إمكان تحقيق الاكتفاء الذاتي في العديد من المنتجات الزراعية، في كلا البلدين، بنسب تصل إلى 100% في كثير من الأحيان، وذلك من جراء تكامل الأنشطة الزراعية فيهما وزيادة كفاءة الانتفاع بالموارد الزراعية المتاحة. It is a strategy demand under globalization conditions for production and economic integration among Arab countries. There is also an increase in the food gap at the level of Arab countries and even at the level of each country. So, it is necessary to find and concentrate on unused agriculture feasibilities or to increase and integrate the efficacy of agricultural material benefits. This study declares the weakness on the efficacy of the use of agriculture materials which are available in Jordan and Syria. There is also in Jordan improper use of agriculture feasibilities as in Jordan there are uncultivated lands. In Syria one of the problems is applying fallow system and improper use of irrigation water by using surface irrigation system. This study also finds that it is possible to achieve self dependence for many agricultural products in both countries with 100%. In most cases as a result of integration of agriculture activities increase the efficacy to get benefits of available agriculture materials.